Emotional Reconstruction of Farmers in Poverty-Alleviated Villages from the Perspective of Emotional Geography: A Case Study of Shibadong Village in Hunan Province - Chen Chirui; He Feng; Tang Fanghua (Redai dili, 2022)
The aim of rural revitalization is to improve the prosperity of farmers. However, farmers are not purely "economics-driven people." In fact, their behavioral logic is driven by internal emotions, which can affect the external environment. At the same time, changes in the external environment can alter a farmer's emotions toward the place. Therefore, research on the emotional reconstruction of farmers in villages where poverty has been alleviated is not only conducive to guiding the direction of construction and governance of such villages and maintaining their harmonious and stable development but also helpful for retaining "returning" farmers. These farmers make up for the absence of the "main body" of the economic development of the village, all of which is significant for the smooth realization of effective connections between poverty alleviation and rural revitalization. For this article, Shibadong Village in Huayuan County, Hunan Province was chosen as the case study, with the "left behind" farmers and "returning" farmers in the village as the research subjects. From the perspective of emotional geography, we used in-depth interviews and participatory observation methods to explore the emotional reconstruction of the farmers and the related mechanism involved under the influence of the targeted poverty alleviation policy. The research showed that 1) the emotional reconstruction of farmers in poverty-alleviated villages mainly includes the reconstruction of five perceptions sense of belonging, sense of happiness, sense of risk aversion, sense of relative deprivation, and sense of loss. 2) The implementation of the targeted poverty alleviation policy has optimized or improved the material space, industrial structure, economic income, and governance services of poverty-alleviated villages, resulting in increases in the farmers' senses of local belonging and happiness and a decrease in their sense of risk aversion. However, an imbalance in poverty alleviation efforts leads to an enhancement of their sense of relative deprivation. The dissolution of traditional cultures and the reconstruction of social relationships result in the farmers feeling lost. These five senses of emotions affect and restrict one another. 3) In the process of emotional reconstruction of farmers in poverty-alleviated villages, the cognition of the individuals is the core force of the process. However, farmers find it difficult to make long-term and wise decisions because of their low cognitive level, which is not conducive to the positive development of emotions. As the leading force driving the emotional reconstruction of farmers, the government—through various poverty alleviation measures—coordinates the order of other individuals participating in poverty alleviation governance, optimizes the rural regional system in the poverty relief village, and improves the farmers' cognition to reshape their local emotions. Enterprises play an auxiliary role in this process, participating in poverty alleviation in various ways. In addition, they facilitate the market economy in optimizing the allocation of resources and improving both the efficiency of poverty alleviation and the resilience of poverty-alleviated villages to resist risks. To consolidate the achievements of poverty alleviation and realize rural revitalization, poverty-alleviated villages should take relevant measures based on the characteristics of emotional space, time, sociality, and hierarchy to cultivate positive emotions, and reduce negative ones, in the farmers. Use of the "place-emotion-behavior" analysis model is helpful for elucidating the interactive processes between the emotions, behaviors, and social material environments of farmers and the significance of those individuals in the reconstruction of the rural regional system in the context of macro policies. This article provides a useful reference for promoting the effective connection between targeted poverty alleviation and rural revitalization.